2010
DOI: 10.1021/pr100047q
|View full text |Cite
|
Sign up to set email alerts
|

Species Differentiation of Seafood Spoilage and Pathogenic Gram-Negative Bacteria by MALDI-TOF Mass Fingerprinting

Abstract: Species differentiation is important for the early detection and identification of pathogenic and food-spoilage microorganisms that may be present in fish and seafood products. The main 26 species of seafood spoilage and pathogenic Gram-negative bacteria, including Aeromonas hydrophila, Acinetobacter baumanii, Pseudomonas spp., and Enterobacter spp. among others, were characterized by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) of low molecular weight proteins ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 56 publications
5
74
0
Order By: Relevance
“…Of note, spectra derived from members of the genus Serratia were different from those of other members of the Enterobacteriaceae. The authors also noted important similarities in spectra between organisms that are genetically closely related as well as organisms found in similar niches (i.e., marine environments) (124).…”
Section: The Enterobacteriaceaementioning
confidence: 99%
See 1 more Smart Citation
“…Of note, spectra derived from members of the genus Serratia were different from those of other members of the Enterobacteriaceae. The authors also noted important similarities in spectra between organisms that are genetically closely related as well as organisms found in similar niches (i.e., marine environments) (124).…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…Böhme et al documented the accuracy of the Bruker BioTyper system for identification of 30 Enterococcus spp. isolated from blood cultures (124). In a study of E. faecalis dental isolates from European countries, MALDI-TOF MS was able to be used to perform cluster analysis by using MicrobeLynx software (Waters).…”
Section: Enterococcus Sppmentioning
confidence: 99%
“…Acquired bacterial MALDI-TOF MS fi ngerprints are matched against spectral libraries previously collected under identical MALDI conditions without further identifi cation. Consequently, identifi cation success remains highly dependent on the number of well characterized food pathogen biomarker sequences available in reference databases that are in the majority of cases still not publicly available (142)(143)(144). It has been demonstrated that sample preparation is also a critical point that includes destruction of bacterial cells and reproducible digestion of liberated proteins (145)(146)(147).…”
Section: Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…The same MALDI-TOF MS fingerprinting approach was previously used by Böhme and colleagues [97][98] Although these authors mainly isolated most of the bacteria from collected cultures, specific gram-negative strains such as Serratia marcescens, Stenotrophomonas maltophilia and Pseudomonas fragi were selected from processed seafood, fresh and frozen tuna Thunnus alalunga and from sardins, respectively [97], whilst the gram-positive strains Staphylococcus aureus, Carnobacterium maltaromaticum, C. Maltaromaticum, Bacillus subtilis, B. licheniformis and B. Megaterium were selected strains were from a shelf-life study of vacuum-packed seafood products that were subjected to a mild heat treatment and stored refrigerated [98].…”
Section: Bacteria Detectionmentioning
confidence: 99%